STRATEGI PEMBERDAYAAN MASYARAKAT OLEH BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN KUTAI KERTANEGARA DALAM MEWUJUDKAN DESA TANGGUH BENCANA (STUDI PADA DESA LOA IPUH DAN DESA PURWAJAWA KABUPATEN KUTAI KERTANEGARA) - Arwanto Harimas Ginting; Tri Dewi (Fakultas Hukum Tata Pemerintahan, 2020)
The purpose of this research is to find out the strategy of BPBD Kutai Kertanegara Regency in disaster mitigation efforts to support an independent society so that later the performance program can be sustainable. In addition, it is also to determine the level of community participation in disaster mitigation efforts, whether the community can participate optimally with the existence of Destana. The method used is descriptive qualitative case study, where the researcher uses two data sources, namely primary and secondary. Primary data is obtained directly from the field while secondary data is not obtained directly in the field, through observation and documentation. The results of this study are that there are several strategies of BPBD Kutai Kertanegara Regency in maximizing community participation, including socialization and training carried out in stages, Destana development involving the community. In addition, community participation is high even though it is hindered by community professions. Community involvement in these areas cannot be separated from people's awareness of their disaster-prone areas so that awareness has opened their minds to participate and participate in disaster resilient village programs. Keywords: Strategy, Empowerment and Resilient Village Disaster